The role of B lymphocyte subsets in nephrotic syndrome: functions, mechanisms, clinical significance and future perspectives - Liao, Yuheng; Hu, Haofei; Wan, Qijun; Song, Haiying (Frontiers in Immunology, 2025)
B lymphocytes play a critical role in the pathogenesis of nephrotic syndrome (NS). This comprehensive review explores the phenotypic characteristics, pathogenic mechanisms, and clinical translational value of B cell subsets in different types of nephrotic syndrome. Studies demonstrate that B cells participate in disease development through multiple mechanisms, including autoantibody production, T cell function regulation, and cytokine secretion. In minimal change disease, B cell-mediated immune dysregulation is primarily characterized by decreased CD19+ cells and increased plasmablasts. Membranous nephropathy patients exhibit increased naïve B cells and decreased memory B cells, while focal segmental glomerulosclerosis is characterized by elevated class-switched memory B cells. These B cell subset alterations can serve as biomarkers for disease activity assessment and prognosis prediction. B cell-targeted therapies, such as anti-CD20 monoclonal antibodies, have demonstrated significant therapeutic efficacy in nephrotic syndrome, further confirming the pivotal role of B cells in its pathogenesis. Different pathological types of NS show significant differences in B cell subset changes, pathogenic mechanisms, and therapeutic responses. Primary and secondary nephrotic syndrome exhibit important distinctions in B cell activation mechanisms, subset imbalance patterns, degree of renal tissue infiltration, and autoantibody profiles. Age factors significantly influence B cell development, function, and therapeutic response, with notable differences between pediatric and adult patients in B cell subset distribution, treatment efficacy, and pharmacokinetics. With the application of emerging technologies such as single-cell sequencing, in-depth analysis of B cell subset characteristics and their interactions with other immune cells will provide new insights for developing more precise diagnostic and therapeutic strategies. However, current methodological heterogeneity challenges in research, including patient population differences, inconsistent B cell subset definitions, technical platform variations, and non-uniform clinical assessment criteria, limit the comparability of research results and clinical applications. Future efforts need to establish standardized B cell monitoring protocols and precision diagnostic systems, develop next-generation B cell-targeted therapeutic strategies, and deeply explore age-specific mechanisms and systems biology research to achieve precision medicine in nephrotic syndrome.